Potensi Aktivitas Antibakteri Ekstrak Etanol Kombinasi Tanaman Herba Ziziphus mauritiana L., Ocimum basilicum Linn. dan Peperomia pellucida L. Kunth Terhadap Staphylococcus Aureus - Fadiya , Faras; Fadila, Safira; Safrina, Safrina (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
The study of the combination of herbal plant extracts has become the subject of intensive research to increase the effectiveness of antibacterials in the application of traditional medicine utilization. The study of the combination of herbal plant extracts has become the subject of intensive research to increase the effectiveness of antibacterials in the application of traditional medicine utilization. This study aims to determine the inhibitory power of the combination of medicinal plant ethanol extracts, namely the combination of bidara leaves (Ziziphus mauritiana L.): suruhan herb (Peperomia pellucida L. Kunth); and basil leaves (Ocimum basilicum Linn.):suruhan herb (Peperomia pellucida L. Kunth) against the growth of Staphylococcus aureus. This study is an experimental laboratory study with phytochemical testing, microbiological testing using the disc diffusion method, and analysis of variance (ANOVA) on the inhibitory power of the combination of medicinal plant ethanol extracts, namely the combination of bidara leaves:suruhan herb and basil leaves:suruhan herb, against the growth of Staphylococcus aureus. The results of the phytochemical test showed that the extracts of bidara leaves, basil leaves, and suruhan herbs contain secondary metabolite compounds, namely alkaloids, steroids, saponins, flavonoids, and phenolics. The combination of suruhan herb:bidara leaves (HS:DB) and suruhan herb: basil leaves (HS:DK) extracts has antibacterial activity against Staphylococcus aureus, as indicated by the formation of an inhibition zone in each comparison. The mix of HS:DB and HS:DK extracts is the most effective at killing Staphylococcus aureus bacteria, with an inhibition zone diameter of 16.07 mm for HS:DB and 15.5 mm for HS:DK. The average area of the inhibition zone is half the area of the inhibition zone in the positive control (ciprofloxacin), with an average of 32.70 mm. The results of the one-way ANOVA test continued with the Duncan test, which stated that each single treatment and combination of extracts were able to inhibit the growth of Staphylococcus aureus, which showed a P value of 0.05.